Edugame Interaktif Cuci Tangan Dalam Meningkatkan Keterampilan Perilaku Hidup Bersih pada Anak Sekolah Dasar - Yoyoh, Imas; Sekarsari, Rita; Hasan, Roswita (Yayasan Daarul Huda Kruengmane, 2024)
Clean and healthy living behavior (PHBS) is an important factor in preventing infectious diseases among elementary school children. One of the main aspects of PHBS is the habit of washing hands properly. However, many students still do not have good handwashing skills due to lack of understanding and less interesting learning methods. Interactive edugames are one of the innovative methods in improving clean living behavior skills in elementary school children. This community service activity aims to increase awareness and skills in clean living behavior through Interactive Handwashing Edugames in washing hands properly. The methods used include the stages of designing game-based education, socialization to students, and evaluating effectiveness through measurements before and after the intervention. The results showed an increase in students' understanding and skills in washing hands properly after using interactive edugames. Thus, this edugame can be an alternative as an effective educational method in increasing health awareness and forming clean living habits from an early age.